The Economics of Recycling Heterogeneity - Don Fullerton; Thomas Kinnaman (CESifo GmbH, 2024)
This paper summarizes the economics perspective on recycling of municipal solid waste. The first section reviews recent data on recycling rates in the United States and across all OECD countries. The OECD data suggest the average aggregate recycling rate across member countries appears to have plateaued over the past several decades. Data from the United States on recycling rates for some common recyclable materials remain low, even after several decades of learning and participation. These data collectively suggest that major new policies may be required to reach increased recycling rate targets. But basing policies on reaching a single aggregate recycling goal, a common practice in past decades and enacted recently in both the Unites States and European Union, may no longer be effective. We discuss many sources of heterogeneity within the recycling industry that have been largely ignored in existing economics literature. Heterogeneity emerges because recyclable materials are very different from each other. Economies and natural environments also differ across both space and time. Recycling policies that ignore these differences are likely to be set inappropriately. If transactions costs are low enough to set a unique recycling policy for each material, in each locality, then a surgical recycling strategy may better serve society. Most jurisdictions have implemented specific recycling policies for products such as automobile batteries that differ greatly from policies enacted for yard waste, because these two materials are very different from each other. A surgical recycling policy would extend this practice, so that the recycling policy for aluminum cans could differ from that of plastic jugs or glass bottles. Reaching future recycling goals could be frustrated by ignoring the sources of heterogeneity across materials, locations, and time.
Keywords: H23; Q38; Q52; Q53; 330; recycling; solid waste; landfill; disposal; dumping; environment; litter; policy; product design